2004
DOI: 10.1086/380910
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparumClonal Population Dynamics during Malaria Treatment

Abstract: We have developed a new fragment-analysis method to enumerate the clones and to quantify their proportions within Plasmodium falciparum isolates. We prospectively enrolled 20 adult patients with uncomplicated malaria who were returning to France from various sub-Saharan countries, from January 2000 through July 2001. The analysis of clonal populations was performed on blood samples obtained at 10 times: 1 before treatment with oral quinine and 9 during the first 96 h of the treatment. The resistance genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 38 publications
2
67
0
5
Order By: Relevance
“…The presence of minority drug-resistant variants is consistent with results of other studies, which have shown patients with genotypicaly wild-type infections before therapy exhibiting genotypicaly mutant infections after unsuccessful chemotherapy (14,15). In Malawi, where chloroquine was replaced with sulfadoxine-pyrimethamine in 1993, the prevalence of the resistance marker pfcrt 76T, as determined by PCR, has been reported to have almost disappeared (6)(7)(8)(9).…”
Section: Discussionsupporting
confidence: 88%
“…The presence of minority drug-resistant variants is consistent with results of other studies, which have shown patients with genotypicaly wild-type infections before therapy exhibiting genotypicaly mutant infections after unsuccessful chemotherapy (14,15). In Malawi, where chloroquine was replaced with sulfadoxine-pyrimethamine in 1993, the prevalence of the resistance marker pfcrt 76T, as determined by PCR, has been reported to have almost disappeared (6)(7)(8)(9).…”
Section: Discussionsupporting
confidence: 88%
“…A higher yield might have been obtained using an advanced method of extracting DNA. Even if DNA is successfully extracted, PCR may fail to detect all genotypes present in a mixed-clones infection both at baseline and at the time of parasite recurrence because some might be present below PCR detection level (Jafari et al 2004) or might be sequestered. However, some evidence indicates that symptomatic infections are less complex than asymptomatic ones.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was prepared by Chelex extraction, as previously described (Plowe et al 1995). A fluorescent PCR analysed block 2 of the msp-1 and of msp-2 domains, as described (Jafari et al 2004). Primers were: msp-1 f-5¢-CACATGAAAGTTATCAAGAACTTGTC-3¢ 1993).…”
Section: Dna Preparation and Pcr Amplificationmentioning
confidence: 99%
“…Primers were: msp-1 f-5¢-CACATGAAAGTTATCAAGAACTTGTC-3¢ 1993). Amplification products were processed in an ABI Prism 310 Genetic analyser (Perkin Elmer Applied Biosystems) and analysed using Genescan software (Applied Biosystems) (Jafari et al 2004). Each genotype is characterized by its size and the area under the curve (AUC) of the peak corresponding to msp-1 or msp-2 PCR products.…”
Section: Dna Preparation and Pcr Amplificationmentioning
confidence: 99%